THU0022 Replication analysis of gene-gene interaction between HLA-DQA2 and HLA-DQB2 variants in italian rheumatoid arthritis patients. (15th June 2017) - Andreasi, R Bassi; Khan, MFJ; Galuppi, E; Govoni, M; Rubini, M
Abstract : Background: Rheumatoid Arthritis (RA) is a complex and multifactorial disease, caused by multiple interactions between genetics and environmental factors. In the context of RA genetics, the Human Leukocyte Antigen (HLA) exerts a primary role. Approximately 90% of RA patients show alleles at the HLA-DRB1 locus, codifying for 5 Amino Acids, known as " shared epitope " (SE). SE is associated with increased risk to develop RA and more severe phenotype, but it does not entirely explain HLA contribution to disease risk. Moreover, it is generally accepted that occurrence risk could be determined by specific gene-gene interactions. A study carried out in USA (NARAC) reported a particular interaction between SNPs in the HLA class II region: HLA-DQA2 (rs9275595) and HLA-DQB2 (rs10807113). Results showed 11 fold increased risk to develop RA in patients carrying both variants (Liu et al ., 2011), while single variants did not significant contribute to the RA risk (Odds ratio, OR, respectively, 1.6 and 1.0). Gene-gene interaction between HLA-DQA2 and HLA-DQB2 SNPs is remarkable, considering that glycoproteins codified by these genes combined each other and create a quaternary structure. Objectives: To replicate NARAC study evidence in Italian population, we genotyped rs9275595 (HLA-DQA2) and rs10807113 (HLA-DQB2) variants using a case/control model. Methods: The study included a cohort of 316 Italian RA patients and a matched group of 443 healthy control individuals. All subjects were genotyped for HLA-DQA2 T>C (rs9275595) and HLA-DQB2 A>C (rs10807113) using TaqMan technology and Real-Time PCR. Results: Replication test performed in our Italian RA cohort did not identify significant interaction between two variants analyzed. However, considering the single variant rs9275595, the results showed a significantly increased risk to develop RA. Taking T/T genotype as the reference, C/C homozygotes showed significant association with a 3.82 fold increased risk of RA (OR=3.821 95% CI (2.017–8.351) p-value=0.00063). The SNP acted under an additive model: T/C heterozygotes showed significant OR=1.988 (95% CI 1.458–2.711, p-value=0.00002). Conclusions: The results of this study do not confirm the gene-gene interaction previous reported in the NARAC cohort (Liu et al ., 2011). However, outcomes suggest that HLA-DQA2 rs9275595 could contribute to RA pathogenesis in the Italian population. References: Liu C, Ackerman HH, Carulli JP. A genome-wide screen gene-gene interactions for rheumatoid arthritis susceptibility. Hum Genet. 2011 May;129(5):473–85. Disclosure of Interest: None declared